Dynamics of traffic flow in lattice model - GUO Wei-ping; WANG Xiao-fan; LI Xiang (Tongxin xuebao)
Based on the lattice network model,three factors affecting the efficiency of network traffic were investigated: routing algorithm,router performance and user’s strategy,and three alternatives to improve the efficiency of communica-tion network traffic were further figured: chose different routing variable according to the loads of the network,made use of advanced routing equipments and adjusted the creation probability of data in the light of users’ feedback strategy.